America's Crisis of Values : Reality and Perception - Baker, Wayne (New Jercy Princeton University Press, 2005)
Is America bitterly divided? Has America lost its traditional values? Many politicians and religious leaders believe so, as do the majority of Americans, based on public opinion polls taken over the past several years. But is this crisis of values real? This book explores the moral terrain of America today, analyzing the widely held perception that the nation is in moral decline.
Includes Illustration and Index.
Keywords: Moral Conditions -- Social Ethics -- Social Values